Stressors faced by healthcare professionals and coping strategies during the early stage of the COVID-19 pandemic in Germany - Frenkel, Marie Ottilie; Pollak, Katja Mareike; Schilling, Oliver; Voigt, Laura; Fritzsching, Benedikt; Wrzus, Cornelia; Egger-Lampl, Sebastian; Merle, Uta; Weigand, Markus A.; Mohr, Stefan (PLOS ONE, 2022)
The COVID-19 pandemic has exerted great pressure on national health systems, which have aimed to ensure comprehensive healthcare at all times. Healthcare professionals working with COVID-19 patients are on the frontline and thereby confronted with enormous demands. Although early reports exist on the psychological impact of the pandemic on frontline medical staff working in Asia, little is known about its impact on healthcare professionals in other countries and across various work sectors. The present cross-sectional, online survey sought to investigate common work stressors among healthcare professionals, their psychological stress as well as coping resources during the pandemic.
Gesehen am 25.01.2022